Recent Advances in the Study of Linguistic Relativity in Historical Context: A Critical Assessment. Issue 3 (26th July 2016) - Lucy, John A.
Abstract : This article outlines the history of empirical research on linguistic relativity, surveys current research, and appraises critically the trends of the past decade, highlighting conceptual and methodological issues. Initial research arose in anthropology from an interest in the significance of language differences for thought, but was soon followed by work in psychology targeting the assessment of language and thought connections. During a subsequent period, efforts were made to synthesize these approaches, yielding two dominant lines of research, one structure‐ and one domain‐centered, both shaped by new input from those studying language acquisition. The contemporary period is marked by an expanded focus on varieties of linguistic input (e.g., deaf and multilingual speakers) and by greater effort to understand the conditions and mechanisms shaping cognitive effects. Overall, research continues to be marked by a tension between the requirements for adequate linguistic analysis and the requirements for effective cognitive assessment.